Heat pipe based thermal management of electrical machines – A feasibility study. (1st August 2022) - Wrobel, Rafal; Reay, David
Highlights: HP-based thermal management of electrical machines offers significant performance gains. Winding active region is best suited for both primary and supplementary HP heat removal. The additional power losses and heat transport offered by HPs need to be well balanced. The initial hardware evaluations confirm validity of the model theoretical assumptions. Abstract: In this paper the use of off-the-shelf heat pipes (HPs) are assessed for the thermal management of electrical machines. The stator-winding assembly has been selected to assess the suitability and effectiveness of cooling systems based upon HPs. The proposed approach targets the main heat source in electrical machines, which is generally associated with the winding subassembly. Two thermal management systems are investigated from a conceptual point of view. The first one uses HPs to improve heat removal for a machine with conventional cooling, e.g. a liquid or air-cooled housing. The second variant uses HPs as the main heat transfer route, e.g. a fully enclosed machine with no integrated, actively cooled housing. Both active- and end-winding regions are considered for direct heat removal from the winding body using HPs. The analysis of the electromagnetic and thermal compatibility of the proposed HP-based thermal management systems is via three-dimensional (3D) finite element analyses (FEAs). It is theoretically shown that the winding active region is better suited for effective HP-based thermal management, compared with the end-winding alternative. Also, the results suggest that proposed thermal management systems allow for a considerable improvement in heat removal from the machine body, up to 43 % and 25 % for the concepts one and two respectively (applied to the winding active region) respectively, as compared with a more conventional heat removal system. The overall performance gains of course depend upon the specific manufacture and assembly processes used in construction of the stator-winding. The initial results from tests on the hardware subassemblies confirm validity of the theoretical methods employed in this feasibility study.